Choice of court agreements under Private International Law and general terms and conditions within unilateral commercial documents: an analysis in light of the Resolution of the Civil and Criminal Court Nº 2 of Miranda de Ebro, Nº 17/2022, dated 21 January 2022 - Lana Arceiz , Víctor Javier; Pérez de Ayala Bonelli, José Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Choice of court agreements included within in general terms and conditions generally result in conflict in practice: in the absence of express acceptance, it is not easy to determine when the arties’ conduct makes it possible to establish tacit acceptance. The problem becomes more complex when the general terms and conditions are part of unilateral documents (e.g. invoices, order confirmations, etc.), issued in the commercial dynamics of the parties at a later point in time than the expression of contractual consent. This article analyses these issues in light of the Resolution of the Civil and Criminal Court Nº 2 of Miranda de Ebro, dated 21 January 2022.
Keywords: Choice of court agreements; general terms and conditions; unilateral commercial documents; Lugano Convention